THE INFLUENCE OF GOING CONCERN OPINIONS, MEASURES AND PROFITABILITY ON AUDITORS SWITCHING - Luki Arsih (Jurnal Ekonomi, 2021)
Auditor switchingis the process of changing the Public Accounting Firm (KAP) carried out by the company. Auditor switching in Indonesia can be done mandatory or voluntary. It is this voluntary auditor switching that raises suspicion from stakeholders to find out the cause. The purpose of this study was to analyze the effect of going concern opinion, KAP size and profitability on auditor switching. The results of this study indicate that the variables of going concern opinion, KAP size and profitability have no effect on auditor switching. The value of Nagelkerke R Square is 0.029, which means that the variability of the dependent variable that can be explained by the independent variable is 2.9%, while the remaining 1.9% is explained by other variables outside this research model. Suggestions for further research to have extensive information about the object of research, use other measures on the same variable, and add other variables for further research.